Xenodon pulcher (Jan, 1863) (Serpentes: Dipsadidae) first record for Brazil and a distribution extension - Cabral, Hugo (2015)
Xenodon is a South American snake genus with 11 species distributed from Guyanas, Brazil, Uruguay, Bolivia, Paraguay and Argentina. Xenodon pulcher is known from Argentina, Bolivia and Paraguay, associated to Chaco ecoregion. After a revision of material located in the Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul (ZUFMS) we found specimens of Xenodon sp. from Porto Murtinho municipality bordering Paraguay, a small area in Brazil harboring chaco vegetation. Ventral, subcaudales, pre-oculars scales and complete triads in the body and tail of 23 specimens of X. pulcher from Paraguay, 32 of X. mattogrossensis from Brazilian pantanal and four specimens of Xenodon sp. collected in Porto Murtinho, Mato Grosso do Sul, Brazil. There is a high variation and overlap between the characters of X. pulcher and X. mattogrossensis; however X. mattogrossensis differs from X. pulcher and X. semicinctus in the presence of lateral white spots on the black rings, and the specimens from Porto Murtinho do not have these spots. This is the first record of the species in Brazil.